Effect of dietary fermented mushroom bed on egg production in laying hens. Issue 11 (2nd November 2017) - Yoshida, Shu; Mitani, Hiroaki; Kamata, Masato; Ohtsuka, Akira; Otomaru, Konosuke; Obi, Takeshi; Kanouchi, Hiroaki
Abstract: Egg productivity is declined by stress. It has been reported that some food supplements can improve the egg productivity due to a reduction of environmental stress. We evaluated the effect of fermented waste mushroom bed (FWMB) as a dietary additive on egg productivity. Hens were fed control food (control group, n  = 100) or 3% FWMB-added food (FWMB group, n  = 100) for 16 months. The number of eggs, soft-shelled eggs, and broken eggs were recorded for 15 months. We also evaluated stress-related markers (ovotransferrin, lipid peroxide, and the heterophil-to-lymphocyte ratio). The FWMB group had slightly increased egg production compared with control hens. The FWMB group produced significantly less broken and soft-shelled eggs than the control group. All stress-related markers were significantly lower in the FWMB group than in the control group. Gut flora was also affected by FWMB feeding. The increased egg production and decreased proportion of broken and soft-shelled eggs might be related to the prevention of stressful conditions by FWMB. Abstract: : Hens were fed 3% FWMB added to the diet. Comparing the egg production between the control group and FWMB group in each month, blood stress markers were improved by FWMB feeding.